PENGUJIAN TINGKAT AKURASI QUALITY CONTROL CAMERA PADA PART COVER VELG - Awaludin, Rizky (Nozzle : Journal Mechanical Engineering, 2024)
In light of the up-and-up of the up-and-up of the up-to-earth, it's need to be a first-time ed in an in-the-world in-the-art control and the most known quality controls. In the manually crafted either of these, the totals were good and No Good. The part that will be at the velg disk is part of velg's. A high-of-a-body part is a part that has no seditions, instuitionless and unsyitioning ones and for the part that is not on a highly dosed part is part that there are some stakes of doubt, for example approval, a light and silver. The used one is to designate on the other part that has been manually in a properly- checked part by the number of his or her designated attributes. For his self-surveying time is to have a part of a velg's work on theveyor, and see the results of each part of the survey on the In-Power Personal Computer, for data that have been served on the In-Personal Computer, recording and re-checking the comquision-ed. In the capacity of the adilics that come up, thekankan color will be in color to the color ofhis sealing, for the abu color means his fountain is a pain, light-and-light light-ass color means silver and the old color of the light of the light, and that of old,... The result of this work's results in the 100% of the 10 part's quality control, 5 part of which are of quality and 5 part that are not of quality and for the seals that can be read by the Quality Control There are also other right-to-doses for the quality control of the light, silver and a pain.